ANALISIS KESALAHAN BERBAHASA DALAM BROSUR PPDB (PENERIMAAN PESERTA DIDIK BARU) SMA SEDERAJAT KABUPATEN BOYOLALI - Wachidah, Mifta (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2019)
The study entitled â€œAnalysis of Language Errors in The PPDB Brochure (Acceptance of New Students) of the senior highschool in Boyolali Districtâ€ aims to describe the language errors contained in the PPBD highschool equivalent brochure in Boyolali regency. In examining this reasearchers used qualitative describtion method, so researchers tried to describe the form or type of language errors found in the brochure. The research data is in the form if words, phrases, and sentences contained in the brochure. The source of the data in this study is the PPDB senior highschool advertisement that equivalent in Boyolali regency. The data collection techniques are by (1) direct observation by looking for the PPDB seniorhighschool equivalent level in Boyolali Regency, both print and online; (2) reading brochures obtained; (3) record and mark language errors. While the data analysis techniques are, (1) reading brochures that have been obtained (2) record any errors encountered; (3) classifying errors; (4) analyze data; (5) presenting data. The results of this study were found to be errors in the spelling level, morphology, punctuation, word selection or diction, and word writing.